Loss of large dendritic spines during normal aging is mediated by alterations in discrete protein networks within the precuneus. (20th December 2022) - Krivinko, Josh; Sui, Zhiyu; Happe, Cassandra; Hensler, Christopher; McKinney, Brandon; Newman, Jason; Ding, Ying; MacDonald, Matthew; Sweet, Robert
Abstract: Background: Loss of dendritic spine density in neocortical areas is a well‐known correlate of cognitive decline in Alzheimer Disease (AD), while preservation of dendritic spines in subjects containing AD‐related pathology is associated with cognitive resilience. Because normal aging is itself associated with dendritic spine loss, identifying upstream mediators of dendritic spine loss may provide an opportunity to develop targeted pharmacotherapies which enhance cognitive resilience and protect against dementia onset. We therefore quantified dendritic spine density and the abundance of over 5000 proteins in the precuneus, a cortical region that is selectively vulnerable early in AD progression. Method: The right precuneus was isolated postmortem from 98 subjects, ages 20‐96 years, none of whom had a documented neurocognitive disorder. Quantitative immunohistochemistry and spinning disk microscopy were used to estimate dendritic spine density by detecting colocalization of spinophilin and filamentous actin. Gray matter was biochemically fractioned into cellular homogenate and synaptosome fractions, and protein abundance was quantified by liquid chromatography/tandem mass tag mass spectrometry. Proteins were assembled into correlated networks using Weighted Gene Co‐expression Network Analysis (WGCNA), and a statistical mediation analysis was used to identify protein networks which mediate the effect of age on dendritic spine density. WebGestalt was used to identify enrichment for gene ontology terms for protein networks relative to a background of all proteins detected in homogenate. Result: The density of large dendritic spines exhibited a negative correlation with increasing age (Pearson R= ‐0.36, p<0.001) (Figure 1). A total of 1839 of 5032 proteins detected in cellular homogenate and 914 of 4754 proteins detected in synaptosomes was significantly correlated with age (q<0.05). Proteins segregated into 19 network modules, five of which significantly mediated the effect of age on dendritic spine density. The modules were enriched for gene ontology terms including "positive regulation of excitatory postsynaptic potential" (enrichment ratio=11.0, p=0.034), "neurotransmitter transport" (enrichment ratio=3.9, p=0.003) and "myelination" (enrichment ratio=21.5, p=<0.001). Conclusion: Density of large dendritic spines declines linearly with age within the precuneus. Network analysis revealed a novel role for myelination by oligodendrocytes in spine loss, identifying a potential target to increase cognitive resilience during aging.